2014
DOI: 10.2147/ijn.s64267
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of endothelial exosomes as carriers for small interfering ribonucleic acid delivery

Abstract: Exosomes, one subpopulation of nanosize extracellular vesicles derived from multivesicular bodies, ranging from 30 to 150 nm in size, emerged as promising carriers for small interfering ribonucleic acid (siRNA) delivery, as they are capable of transmitting molecular messages between cells through carried small noncoding RNAs, messenger RNAs, deoxyribonucleic acids, and proteins. Endothelial cells are involved in a number of important biological processes, and are a major source of circulating exosomes. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Briefly, to load EVs with heterologous siRNAs, isolated EVs are mixed with the siRNAs, then incubated on ice for 10 min and exposed to an electric field pulse [15]. Importantly, other studies have also shown that heterologous small RNAs, delivered by EVs, are functional in recipient cells [102,107,108].…”
Section: Oviductosomes: Potential Tools For Delivering Exogenous Nuclmentioning
confidence: 99%
“…Briefly, to load EVs with heterologous siRNAs, isolated EVs are mixed with the siRNAs, then incubated on ice for 10 min and exposed to an electric field pulse [15]. Importantly, other studies have also shown that heterologous small RNAs, delivered by EVs, are functional in recipient cells [102,107,108].…”
Section: Oviductosomes: Potential Tools For Delivering Exogenous Nuclmentioning
confidence: 99%
“…For example, exosomes from primary aortic endothelial cells were reported to successfully deliver siRNA against luciferase into endothelial cells in a gene-silencing study. 34 However, additional studies are needed to explore if endothelial ECV can successfully deliver different cargo molecules into the brain as well.…”
Section: Ecv As Drug Carriers Into the Cnsmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) images of negatively stained exosomes initially indicated a cup-shaped morphology, yet later cryo-electron microscopy images of unfixed exosomes, including in a study by Banizs et al, comparing negative-stain EM and unstained cryo-EM of the same exosome preparation, showed a spherical shape, suggesting that the cup-shaped morphology might have resulted from the fixation process in conventional TEM (Figure 2; Théry et al, 2006;Raposo and Stoorvogel, 2013;Banizs et al, 2014).…”
Section: Introductionmentioning
confidence: 99%